The self-regulation of motivation: Motivational strategies as mediator between motivational beliefs and engagement for learning. (2017) - Smit, Karin; de Brabander, Cornelis. J.; Boekaerts, Monique; Martens, Rob. L.
Highlights: Students in vocational education use motivational strategies to focus on schoolwork. Motivational strategy use partly mediates between value, and effort and pleasure. Autonomy-based strategies have more effect on pleasure than control-based strategies. Studies on training motivational strategies should include increasing value-belief. Abstract: In this research we studied studentś use of motivational strategies as mediator between motivational beliefs and motivational engagement. Dutch students in pre-vocational secondary education (N = 3602, mean age 14) completed a self-report questionnaire on five motivational strategies (Environmental Control, Interest Enhancement, Self Consequating, Performance Self-talk, Mastery Self-talk); motivational beliefs (value attached to schoolwork, competence); and motivational engagement (pleasure, effort, persistence, achievement). A validation of the questionnaire showed a good fit. Structural equation modelling indicated that strategy-use partly mediates the relation between value, and effort and pleasure. Competence showed a weak direct relation with effort an pleasure. No result were found for achievement. Further implications of these findings for practical use and further research are discussed.